ID: 56. Issue 1 (November 2015) - Young, Howard; Valencia, Julio; Bae, Heekyong; Haines, Diana; Lockett, Stephen; Karwan, Megan; Hanson, Charlotte; Barlow, Alec
<x xml:space="preserve">Abstract</x> The success of immunotherapies against melanoma involves the development of autoimmune-type responses due to increases of interferon-gamma (IFN-g). However, attempts to use IFN-g in melanoma have been unsuccessful due to low response rate and significant toxicity. Here, we used the unique features of our mouse model to investigate the anti-melanoma effects of IFN-g on a phenotype based autoimmune background. Syngeneic B16-F10 melanoma cells were injected intravenously (iv.) or subcutaneously (sc) into C57BL/6 mice with deletion of the IFN-g 3′ UTR AU-Rich element (ARE-DEL) region. We found that moderate sustained levels of IFN-g increased significantly (p = 0.02; ANOVA) overall survival (OS) and decreased tumor growth rate (p = 0.0154, ANOVA) compared to wild-type (WT) mice. Necropsy after clinical sacrifice showed significantly less (p < 0.05; ANOVA) organ colonization and ulceration of the skin overlaying the graft in ARE-DEL mice compared to WT control mice. However, evidence of neoplastic emboli causing micro and macro infarctions (such as in salivary glands) more likely affected OS in ARE-DEL mice. Interestingly, melanoma tumors exhibited increased grade of necrosis and macrophage infiltration in ARE-DEL mice suggesting that moderate increases of IFN-g exert anti- metastatic immune response. Live cell imaging and spheroid invasion assays on Matrigel confirmed that pre-treatment with IFN-g for 48 h limited directional movement, dendrite formation, and metastatic ability of B16-F10 cells. Given the lack of consensus on the right dose of IFN-g, our data suggest that sustained moderately high levels of IFN-g hamper B16-F10 melanoma metastasis but enhance the risk of neoplastic emboli.